Fast atomic diffusion in amorphous films induced by laser pulse annealing - Teodorescu, V. S.; Ghica, C.; Maraloiu, A. V.; Kuncser, A.; Lepadatu, A. M.; Stavarache, I.; Ciurea, M. L.; Scarisoreanu, N. D.; Andrei, A.; Dinescu, M. (CAS 2016 proceedings : 2016 International Semiconductor Conference : 39th edition, October 10-12, Sinaia, Romania, 2016)
Fast atomic diffusion was evidenced in the surface layer of amorphous thin films of oxides and semiconductors irradiated with low fluence UV pulse laser. This process takes place in a surface layer with a thickness related to the laser radiation absorption depth in the target material and was revealed by the cross section transmission electron microscopy studies. These high values of diffusivity can be explained by supposing the glass transition transformation in the amorphous structure, triggered by the action of the laser pulse field. This effect can have application for controlling structural modifications at nanoscale of the thin films surface and also for inducing structural modification of interfaces between the film and substrate.